Distinguishing informational from value‐related encoding of rewarding and punishing outcomes in the human brain. (24th May 2014) - Jessup, Ryan K.; O'Doherty, John P.
Abstract There is accumulating evidence implicating a set of key brain regions in encoding rewarding and punishing outcomes, including the orbitofrontal cortex, medial prefrontal cortex, ventral striatum, anterior insula, and anterior cingulate. However, it has proved challenging to reach consensus concerning the extent to which different brain areas are involved in differentially encoding rewarding and punishing outcomes. Here, we show that many of the brain areas involved in outcome processing represent multiple outcome components: encoding the value of outcomes (whether rewarding or punishing) and informational coding, i.e. signaling whether a given outcome is rewarding or punishing, ignoring magnitude or experienced utility. In particular, we report informational signals in the lateral orbitofrontal cortex and anterior insular cortex that respond to both rewarding and punishing feedback, even though value‐related signals in these areas appear to be selectively driven by punishing feedback. These findings highlight the importance of taking into account features of outcomes other than value when characterising the contributions of different brain regions in outcome processing.